Kedudukan Artificial Intelligence (AI) di dalam Hukum Perdata Serta Pertanggungjawaban Pengguna Atas Penyalahgunaannya - Dwi Natalia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Artificial intelligence is a technology created with the purpose of being programmed like human intelligence in general into electronic media so that it can think and perform tasks like a human. Position or status is an important matter in law, especially in civil law. The position of artificial intelligence itself is not yet known in civil law, as it is still considered merely as an object or legal thing. Actions carried out by artificial intelligence created to act like humans raise questions in society regarding its position. With the design of AI or artificial intelligence similar to humans, if the AI then commits an act that can cause harm, it cannot be held accountable for its illegal actions that may result in losses. Besides the positive impacts provided to society, negative impacts cannot be avoided, which brings back into question the responsibility of artificial intelligence or AI in relation to its position in civil law. In this study, normative research with a juridical approach was used as the research method, which refers to the existing laws and regulations in Indonesia.Â Â